Condiciones de trabajo y de seguridad social en asociaciones de pequeños y medianos agricultores campesinos con prácticas de economía solidaria en tres municipios del oriente antioqueño, Colombia, 2015 (2019)
ABSTRACT: The agricultural-based solidarity economy practiced by rural communities in Eastern Antioqua, Colombia, has become a tool for resistance, as well as an alternative source of employment for a socially and economically vulnerable population. Economies based on agriculture and the uncertainties of the productive transformations derived from a community’s proximity to Medellin metropolitan area, are important factors that should be taken into account when examining the potentials of a solidary economy. Objective: To analyze the working and social conditions of a group of small and medium-scale farmers, from 3 towns in Eastern Antioquia, who follow the solidarity economy and are committed to food security. Methodology: A descriptive, transversal study was carried out with 111 active producers belonging to 10 legally consolidated solidarity economy farmers associations. Primary data was gathered through polls and workshops. Variables in respondents sociodemographics, work and social security were analyzed based on the statistical measurements of frequency, proportion and central tendency. Results: 85.6% of respondents are independent workers and belong to a lower socioeconomical strata with a mean monthly income of COP 296.000; 72% have health insurance through the country’s subsidized system; 91% work without occupational hazard insurance; 88.3% do not contribute to a pension fund. Discussion: Income of the surveyed population was found to be lower than both the legal minimum wage and average wages of workers in the same field; income inequalities are very pronounced compared to other Colombian workers; increasing pension enrollment and occupational hazard coverage are challenges the government continues to face. Key words: Farmer economy, farmers associations, agriculture, organic agriculture, social security, employment, Eastern Antioquia